Pavement engineering principles and practice - Mallick, Rajib Basu 1966-; El-Korchi, Tahar (CRC Press, 2013)
"Covering the entire range of pavement construction, from soil preparation to structural design, life-cycle costing, and analysis, this book integrates the concepts of mix and structural design, emphasizing pavement evaluation and rehabilitation techniques. State-of-the-art content introduces the latest concepts, including ground-penetrating radar and seismic testing, legal issues and sustainability, and smart sensors. Fully updated with 75 new images and figures, this new edition covers designs and examples of drainage structures, as well as methods used in forensic investigation to determine type and cause of distress, and collection of environmental data for proper design considerations"-- Provided by publisher.